2022
DOI: 10.3847/1538-4357/ac5d5d
|View full text |Cite
|
Sign up to set email alerts
|

A Single-pulse Study of the Subpulse Drifter PSR J1631+1252 Discovered at FAST

Abstract: We report on the pulse-to-pulse energy distribution and longitude-resolved modulation properties of PSR J1631+1252 discovered by the Five-hundred-meter Aperture Spherical radio Telescope. Our analysis made use of the data acquired at 1250 MHz from the follow-up timing observations that lasted over a year. PSR J1631+1252 has a rotational period of ∼0.310 s, and a dispersion measure of ∼32.73 pc cm−3. The energy distribution is well described by a lognormal distribution, the parameters of which do not vary with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The drift rate of these pulsars is Δf = 0. At present, the mode changing, nulling and drifting subpulse are detected in hundreds of pulsars (Wang et al 2007;Weltevrede et al 2007;Basu et al 2019a;Wang et al 2021;Wen et al 2022). The observation shows that there may be some connection between these three famous pulsar emission variations.…”
Section: Introductionmentioning
confidence: 86%
“…The drift rate of these pulsars is Δf = 0. At present, the mode changing, nulling and drifting subpulse are detected in hundreds of pulsars (Wang et al 2007;Weltevrede et al 2007;Basu et al 2019a;Wang et al 2021;Wen et al 2022). The observation shows that there may be some connection between these three famous pulsar emission variations.…”
Section: Introductionmentioning
confidence: 86%
“…The rapid growth of pulsar discoveries from CRAFTS promotes the international cooperation between CRAFTS and other telescopes, e.g., Parkes, Effelsberg, Green Bank radio telescopes, Arecibo telescope, and Fermi-LAT gamma-ray telescope, for pulsar follow-up and timing studies (Cameron et al 2020;Wang et al 2021aWang et al , 2021bCruces et al 2021;Wen et al 2022;Miao et al 2023). More than 170 new pulsars have been discovered, 6 including 40 millisecond pulsars (Wang et al 2021a;Miao et al 2023), long-period pulsars (Zhang et al 2019;Tedila et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is found that some pulsars exhibit unregular single-pulse emission such as fluctuation in pulse width, pulse phase and pulse intensity (Wen et al 2016). The phenomenon of singlepulse emission variation in pulsars specifically includes nulling (Backer 1970;Ritchings 1976;Wang et al 2007;Gajjar et al 2012;Wen et al 2016), mode changing (Bartel & Hankins 1982;Wang et al 2007;Wen et al 2020;Yan et al 2020), giant pulses (Staelin & Reifenstein 1968;Hankins et al 2003;Kuzmin & Ershov 2006;Sun et al 2021), subpulse drifting (Drake & Craft 1968;Weltevrede et al 2006Weltevrede et al , 2007Basu et al 2016Basu et al , 2019Wen et al 2022) and so on. The investigation of single-pulse emission variation will help us to reveal the physical mechanism of emission for radio pulsars.…”
Section: Introductionmentioning
confidence: 99%
“…The millisecond pulsar PSR J0621+1002 displays periodic pulse intensity modulation (Wang et al 2021a). Wen et al (2022) investigated the single-pulse energy distribution and sub-pulse drifting characteristics of PSR J1631+1252. A study of the newly identified pulsar PSR J1900+4221 discovered by FAST shows that it has an NF of 22% and manifests the mode changing phenomenon (Tedila et al 2022).…”
Section: Introductionmentioning
confidence: 99%